Trustworthy Intra Cluster Management Scheme (TICMS) to Improve Lifetime of Wireless Sensor Networks - N. Geethanjali, S. Suresh Babu (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Wireless Sensor Networks (WSN) place a significant emphasis on energy efficiency because power consumption is the single most important factor in determining the overall lifespan of the network. There have been multiple suggestions made for potential strategies that could reduce the energy consumption of nodes. In this article, a intra cluster management scheme based on trust is provided and it is demonstrated that the method is also energy efficient. The success of the work is dependent on significant phases, which are the network area segregation phase, Cluster building phase includes cluster head node selection, computation of the trust degree & the control of the node’s state and the routing phase. Taking into account the location coordinates allow for the formation of the cluster and the CH node selection. The CH node is responsible for calculating the trust level and maintaining control over the state of the other nodes in the network. The network lifetime is significantly improved, owing to the control over working nodes. The experimental results show that the proposed work is satisfactory with regard to the longevity of the network and energy efficiency.